"Composite Creatures" : Monstrous Women and the Nonhuman in Gregory Maguire’s Wicked: The Life and Times of the Wicked Witch of the West - Lehtonen, Raakel (My University, 2025)
In my thesis I employ ecofeminist theory to analyse Gregory Maguire’s novel Wicked: The Life and Times of the Wicked Witch of the West (1996). As women’s subordination has been justified by their conflation with nonhuman nature, feminism’s relationship to the concept of nature has often been troubled. However, Plumwood (1993) and Alaimo (2000) propose that the woman-nature connection can be reutilised in a manner that does not resort to essentialism. Several scholars have found that Wicked addresses culturally well-established tropes of witches and monstrous women in a subversive manner. In addition, I argue that earth, plant and animal metaphors are employed in a manner that rearticulates the woman-nature confluence. The novel’s use of metaphoric language associates Elphaba and her body with earth, animals and plant life. However, this affinity with nonhuman nature does not reduce Elphaba to the established tropes of naturalised women or reduce her agency. My analysis concerns also the anthropomorphic Animals in the novel. Both Elphaba and animals can be understood as hybrid characters inhabiting liminal positions. However, while hybridity is employed in the novel to break solid categories, it is not depicted as inherently virtuous or unproblematic, but as something that may coexist with ethical issues and violence.
Keywords: ecofeminism, anthropomorphism, hybridity, monsters